KONSEP LA UHIBBU DALAM RETORIKA DAKWAH: ANALISIS PEMAHAMAN DAI TERHADAP FIQIH DAKWAH - Pambayun, Ellys Lestari; Hidayat, Nurwafieq; Prathama, Muhammad Rizki; Samil, Muhammad; Baidhowi, Ahmad Misbah (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2023)
This research aims to explain the concept of la uhibbu and da'wah fiqh in analyzing the reality of the pros and cons of da'wah. Because, the challenges and opportunities of da'wah, as an effort to convey the noble teachings of the Islamic religion, often reap pros and cons from the mad'u or recipient of the da'wah, which are caused by factors of the preacher (communicator), the messages packaged, the media used, on the part of his own mad'u (communication), or how to give feedback to his audience. The aim of the study is to explore and describe the aspects and factors that make preaching unpopular with some individuals. This study was explored using literature analysis methods on references and texts relevant to the theme of this study. The findings explain that several main factors involve the incompatibility of da'wah methods with the social context, a lack of understanding of the audience, and the potential for misuse of da'wah for personal or certain group interests. The results of the discussion explain that the complexity of social dynamics in receiving da'wah requires a more contextual approach and is based on a deep understanding of the needs of the target community